The immunodepressive effect of Friend virus: II. Reduction of splenic haemolysin-producing cells in primary and secondary responses - Wedderburn, Nina (1968)
The effect of Friend virus on the response of Balb/c mice to sheep red cells, as measured by the numbers of haemolytic plaque forming cells in the spleen, was investigated. Virus injected with or before the antigen reduced the numbers of IgM and IgG antibody-producers, the latter more so than the former. Both the primary and the secondary responses were affected. Some possible mechanisms of action of the virus on immune responses are discussed.